The Influence of Resilience on Children's Self-Efficacy in Dealing with the Law at UPTD PPA Makassar City - Magfirah, Jihan; Razak, Ahmad (Polteknik Ilmu Pemasyarakatan, 2024)
Children in conflict with the law (ABH) are those aged 13-18 who are involved in legal issues. ABH often face negative stigma upon reintegration into society, which can lead to negative consequences such as decreased self-confidence and difficulty recovering from poor labels. This study aims to examine the impact of resilience on the self-efficacy of ABH at UPTD PPA Makassar. A quantitative approach was used, involving 91 ABH subjects from various ethnic groups. Data were collected using resilience and self-efficacy scales adapted by the researcher. Purposive sampling was employed. Simple linear regression analysis revealed a significance value of 0.051, indicating a significant effect of resilience on self-efficacy. The R-square value of 0.400 means that 40.0% of the variance in self-efficacy can be explained by resilience, while the remaining 60.0% is influenced by other factors not explored in this study. It is hoped that this research will contribute to the knowledge, especially in the field of social psychology, regarding the impact of resilience on self-efficacy, particularly for children entering adolescence.